Power Communication Actors Cash Social Support Program for Impacted COVID-19 Citizen - Klara Kumala Sari; Ali Hanafiah (Journal of Transformative Governance and Social Justice, 2023)
Government as an important body in the framework of governance. The government must pay attention to peace and public order, the demands and expectations as well as the opinions of the people, the needs and interests of the community, environmental influences, communication and coordination arrangements, the participation of all levels of society and the existence of legitimacy. This study aims to analyze actor relationships by analyzing aspects of social network analysis calculations such as actor popularity (degree), actor closeness to other actors (closeness), and which actor functions as a liaison between one actor and another (betweenness).The mix-method approach is used to answer the problem formulation. Data were obtained through interviews and collecting questionnaires from the actors involved in implementing the cash direct social assistance distribution program in Batu City. Data were analyzed through an interactive analysis model using an analytical tool using social network analysis. The results of this study indicate that each actor involved in implementing the social assistance distribution program for people affected by Covid-19 in Batu City has different networking patterns. The strategic actor in the implementation network for the distribution of social assistance programs for people affected by Covid-19 is the social service. Each actor has their own role, namely the Covid-19 task force unit acts as a program maker. By analyzing communication relationships through social network analysis by focusing on public actor communication, we can find out the actor's communication relationship in the Covid-19 social assistance program.